Diabetes mellitus promotes susceptibility to periodontitis—novel insight into the molecular mechanisms - Zhao, Mingcan; Xie, Yuandong; Gao, Wenjia; Li, Chunwang; Ye, Qiang; Li, Yi (Frontiers in Endocrinology, 2023)
Diabetes mellitus is a main risk factor for periodontitis, but until now, the underlying molecular mechanisms remain unclear. Diabetes can increase the pathogenicity of the periodontal microbiota, and increase the inflammatory/host immune response of periodontium. Hyperglycemia induces reactive oxygen species (ROS) production and enhances oxidative stress (OS), exacerbating periodontal tissue destruction. Furthermore, the alveolar bone resorption damage and the epigenetic changes in periodontal tissue induced by diabetes may also contribute to periodontitis. We will review the latest clinical data on the evidence of diabetes promoting the susceptibility of periodontitis from epidemiological, molecular mechanistic, and potential therapeutic targets, and discuss the possible molecular mechanistic focusing in particular on novel data of inflammatory/host immune response and OS. Understanding the intertwined pathogenesis of diabetes mellitus and periodontitis can explain the cross interference between endocrine metabolic and inflammatory diseases better and provide theoretical basis for new systemic holistic treatment, and promote interprofessional collaboration between endocrine physicians and dentists.